1151 Ethnic minority outcomes in multiple sclerosis. (1st December 2017) - Alsaeed, Meshari; Harding, Katharine; Willis, Mark; Tallantyre, Emma; Wardle, Mark; Pickersgill, Trevor; Robertson, Neil
Abstract : Background: Multiple sclerosis (MS) is most common in patients of Caucasian ethnicity, but little is known about manifestation of disease and long-term outcomes in patients of other ethnicities. Methods: 1866 Caucasian patients and 83 ethnic minority (EM) patients were identified from the south-east Wales MS registry. Student's T-test and chi-squared test were used to test for differences in age at onset, sex ratio, disease course, and annualised relapse rate (ARR). Kaplan-Meier survival analysis was used to investigate time to EDSS 3.0, 4.0 and 6.0. Results: Sex ratio was similar in both groups. EM patients were younger at onset (28.6 versus 32.8 years, p=0.001), and less likely to have primary progressive disease (4.8% versus 11.6%, p=0.032). Although not significant, ARR was higher in EM (0.65 versus 0.55, p=0.076), and ataxia was more common at onset (19.2% versus 12.1%, p=0.062). Time to EDSS 3.0 was shorter for EM (11.6 versus 15.9 years, p=0.009), but there was no difference in later milestones. Conclusion: Presentation of MS may be atypical in EM patients. Early recognition of MS in EM patients will allow timely intervention with DMTs to reduce the impact of relapses and early acquisition of disability.